CORRELATIONS OF MAIN CRANIAL INDEX WITH CHARACTERISTICS OF UPPER AND LOWER JAWS AMONG RESIDENTS IN UKRAINE OF ADOLESCENT AGE - Дмітрієв, М.О. (World of Medicine and Biology, 2016)
Aim of our work – establishing features of correlations major cranial performance with characteristics of the upper and lower jaws in Ukrainian boys and girls. Materials and methodsUsing the device Veraviewepocs 3D, Morita (Japan) in 38 boys (age from 17 to 21 years) and 55 girls (aged from 16 to 20 years) with orthognathic bite were obtained and analyzed side teleradiography and scans.Cephalometric points and measurements were performed according to the recommendations of C. C. Steiner, and anatomical - by Basavaraj Subhashchandra Phulari, S. I. Doroshenko and Ye. A. Kulhynskiy.We determined the following parameters: key parameters of the skull and maxilla that do not change during surgical and orthodontic treatment; angular indicators of maxilla; linear performance of maxilla; angular rates of lower jaw; linear mandible performance; angular between jaw characteristics; linear between jaw characteristics; index between jaw performance.Evaluation of correlations carried out in the license package "Statistica 6,0" using Spearman nonparametric statistics.Results. DiscussionsFound that in young men the value of the basics maxilla has significant direct medium strength (r = from 0.33 to 0.52) links with facial and inclination corners, with angles SNA, SNB, SND, NBa-PtGn, with an effective length of upper jaw, with the length of the upper jaw, with distance PN_A, mandibular length, with distance S_L and the ratio AFH_PFH; credible medium strength reverse (r = -0.37 to -0.48 from) relationships with angles Ar-Go-Me, G, FMA, ML_NSL, SN_GoGn, with the base and basal angles. In girls value basics of the upper jaw has significant direct medium strength (r = 0,52 and r = 0,48) connections with an effective length of the upper jaw and maxilla length.In young men H-angle has significant strengths reverse (r = -0,61 r = -0,62) links with facial angle and angle SNA; direct credible of medium strength (r = from 0.32 to 0.51) connections with angles NL_NSL, ML_NSL, SN_GoGn, with the lower face height, with type face by Schwartz; reverse credible of medium strength (r = -0.39 to -0.59 from) relationships with inclination angle, with angles SNB, SND, with distance S_L. In girls H-angle has a significant direct medium strength (r = 0,30 to 0,56) connections with angles NL_NSL, ML_NSL and SN_GoGn, with distance PN_A, basal and basic angles, type of profile and face by Schwartz; reverse credible medium strength (r = -0.32 to -0.49 from) relationships with face and inclination corners with angles SNA, SNB, SND, with distance and the ratio S_L AFH_PFH.In young men angle NSBA has significant direct medium strength (r = 0,38 and r = 0,39) relationships with NL_NSL angle and with type face by Schwartz; reverse credible medium strength (r = -0.36 to -0.44 from) relationships with face and inclination corners with angles SNA, SNB, SND, with distance S_L. In girls angle NSBA has significant direct medium strength (r = 0,37 both) connections with angles and ML_NSL SN_GoGn; reverse credible medium strength (r = -0,33 and r = -0,41) relationships with SND angle and distance S_L.In young men distance Se_N has credible direct strong (r = 0,66) relationship with the length of the mandible; direct credible medium strength (r = from 0.41 to 0.58) connections with the angle NBa-PtGn, with an effective length of the upper and lower jaw, with the length of the upper jaw, with length of branches of the mandible and the distance S_L; reverse credible medium strength (r = -0.35 to -0.47 from) relationships with angles Ar-Go-Me, G, FMA, ML_NSL, SN_GoGn, U-axis, and basic basal angles; back unreliable medium strength (r = -0,32) connection with a profile angle T. In girls distance Se_N has significant direct medium strength (r = from 0.31 to 0.54) connections with an effective length the upper jaw, maxilla length, effective length mandible and mandibular length, mandibular branch length, distance S_L and AFH, lower the height of the face; credible medium strength back (r = -0,32) connection with distance PN_A.In young men distance S_E has significant direct medium strength (r = 0,35 and r = 0,40) connections with a lower face height and maxillary-mandibular angle; reverse credible medium strength (r = -0.39 to -0.46 from) relationships with facial angles and angles SNA, SNB, SND, distance S_L. In girls distance S_E has significant direct medium strength (r = 0,30 and r = 0,35) relationships with the U-axis, the effective length of the mandible; credible medium strength back (r = -0,30) connection with distance PN_A.
Keywords: cephalometry; odontometry; boys; girls; cranial performance; characteristics of the upper and lower jaws